2014
DOI: 10.3171/2014.4.focus14159
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-based management of traumatic thoracolumbar burst fractures: a systematic review of nonoperative management

Abstract: Object The overall evidence for nonoperative management of patients with traumatic thoracolumbar burst fractures is unknown. There is no agreement on the optimal method of conservative treatment. Recent randomized controlled trials that have compared nonoperative to operative treatment of thoracolumbar burst fractures without neurological deficits yielded conflicting results. By assessing the level of evidence on conservative management through validated methodologie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
43
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 57 publications
(124 reference statements)
1
43
0
3
Order By: Relevance
“…For patients who are neurologically intact, nonoperative treatment may prove sufficient. [6][7][8]10,11,14,[27][28][29] Surgery is undertaken when neurological deficits and/or persistent pain are present, or the fracture is deemed unstable with disruption of the posterior ligaments. In the absence of neurological deficit or biomechanical instability, the decision favoring one approach (surgical or nonsurgical) becomes more contentious and ambiguous.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For patients who are neurologically intact, nonoperative treatment may prove sufficient. [6][7][8]10,11,14,[27][28][29] Surgery is undertaken when neurological deficits and/or persistent pain are present, or the fracture is deemed unstable with disruption of the posterior ligaments. In the absence of neurological deficit or biomechanical instability, the decision favoring one approach (surgical or nonsurgical) becomes more contentious and ambiguous.…”
Section: Discussionmentioning
confidence: 99%
“…The consensus from the aforementioned studies and other meta-analyses is the inconsistency of outcomes, rendering a decision in favor of operative versus nonoperative treatment inconclusive. 8,[29][30][31][32] In our management of neurologically intact burst fractures, with intact PLC or a TLICS score of 2, patients were initially all treated nonoperatively with bracing and gradual mobilization. Thoracolumbar braces were used in all patients, although recent reports have shown that braces did not add sufficiently to clinical outcomes to justify their cost or use.…”
Section: Discussionmentioning
confidence: 99%
“…As with all spinal fractures, those within the lumbar spine can take on a variety of patterns 15 and can range from stable to unstable; most fractures therefore have both operative and nonoperative management options. 1,7,41 The decision to operate is traditionally based on such factors as fracture morphology, integrity of the posterior ligamentous complex, and neurological presentation. 16,39 For the elderly, however, there must also be a careful consideration of perioperative risk (including preexisting comorbidities, premorbid quality of life, and goals of care) versus potential benefit.…”
mentioning
confidence: 99%
“…Thoracic lumbar sacral orthoses (TLSO) are used to facilitate management of spinal fractures and are the most common orthosis used in the conservative management of spinal fractures in the thoracolumbar spine . A TLSO is prescribed when surgical intervention is not required and aids in stabilisation, analgesia and early mobilisation .…”
Section: Introductionmentioning
confidence: 99%